Lessons learned: A critical reflection on child- and contextual variables related to the development of children with a significant cognitive and motor developmental delay. (January 2022) - Van keer, Ines; Dhondt, Ann; Van der Putten, Annette; Maes, Bea
Highlights: The scientific study of this target group is challenging. The development of 45 children (6–59 months) was tracked. Challenges in measurement and analysis of variables were reflected upon. Creativity, perseverance and modesty in generalization is necessary. Abstract: Background: The scientific study of young children with a significant cognitive and motor developmental delay is challenging due to the children's complex disabilities and high demands on family life and professional support. We aim to critically reflect on the measurement and analysis of child- and contextual variables within an ongoing research project on these children's developmental trajectories. Method: The OJKO-project tracked the development of a sample of children ( n = 45) between the age of 6 months and 4 years with a significant cognitive and motor developmental delay, in Belgium and the Netherlands. Results: The complexity of the children's disabilities and daily life context, and subsequent challenges in measurement and analysis of variables, were confirmed and reflected upon. Conclusions: Due to the uniqueness and complexity of this target group, research should be characterized by creativity, perseverance and substantial modesty in the immediate generalization of results.